A topographical organization for action representation in the human brain. Issue 10 (2nd July 2015) - Handjaras, Giacomo; Bernardi, Giulio; Benuzzi, Francesca; Nichelli, Paolo F.; Pietrini, Pietro; Ricciardi, Emiliano
Abstract How the human brain represents distinct motor features into a unique finalized action still remains undefined. Previous models proposed the distinct features of a motor act to be hierarchically organized in separated, but functionally interconnected, cortical areas. Here, we hypothesized that distinct patterns across a wide expanse of cortex may actually subserve a topographically organized coding of different categories of actions that represents, at a higher cognitive level and independently from the distinct motor features, the action and its final aim as a whole. Using functional magnetic resonance imaging and pattern classification approaches on the neural responses of 14 right‐handed individuals passively watching short movies of hand‐performed tool‐mediated, transitive, and meaningful intransitive actions, we were able to discriminate with a high accuracy and characterize the category‐specific response patterns. Actions are distinctively coded in distributed and overlapping neural responses within an action‐selective network, comprising frontal, parietal, lateral occipital and ventrotemporal regions. This functional organization, that we named action topography, subserves a higher‐level and more abstract representation of finalized actions and has the capacity to provide unique representations for multiple categories of actions. Hum Brain Mapp 36:3832–3844, 2015. © 2015 Wiley Periodicals, Inc.